Analysis of Key Mechanics for The Impact of Game Design on Player Experience - Wang, Dongwei (Transactions on Computer Science and Intelligent Systems Research, 2025)
The development of the Internet and technology has transformed the gaming industry, leading to more immersive, evolving games, from 2D to 3D, independent to online, and from simple to highly interactive experiences. This paper explores the relationship between game design and player experience, specifically examining how different game elements influence player immersion, challenge, and emotional feedback. The study employs a combination of literature review and case studies, referencing key mechanics from various popular games and assessing their impact on player experience. The findings suggest that well-designed game mechanics enhance players' positive perceptions of the game and contribute to longer play sessions and sustained engagement. By analyzing the core components that drive player satisfaction, this research highlights the importance of game mechanics in fostering a deeper emotional connection and improving overall gameplay. The study provides valuable insights for game developers aiming to create more immersive and engaging gaming experiences. Future work will explore adaptive game mechanics powered by real-time player analytics, for dynamically tailor experiences to individual preferences.